Implementation of IFRS Convergence and Corporate Supply Chain Management on Earnings Quality (Study on Oil Plantations Companies in Indonesia and Malaysia) - Narumondang Bulan Siregar; Azhar Maksum; Rina Br Bukit; Badaruddin Badaruddin (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to examine the correlations of IFRS implementation and corporate social responsibility on Earnings quality of Indonesia and Malaysia Oil Plantations companies, during the full convergences of IFRS period (2012-2016). The logistics industry is becoming increasingly competitive, and supply chains becoming increasingly complex. This research is using data from the annual financial report issued by the company that is registered at the Indonesian stock exchange and Malaysia stock exchange, from 2012 to 2016. The population of this research is plantation companies that are listed on the Indonesian stock, as much as 15 company and exchange Malaysia, as much as 40 companies. To examine the impact of IFRS convergence and CSR on the quality of earnings of companies listed on Oil Palm Company in Indonesia and Malaysian Stock Exchange, it was tested using SPSS with Canonical Test.Main Findings: The main findings of this study indicate that the convergence of IFRS and CSR has a significant effect on the value of Indonesia and Malaysia Oil Plantation Companies. Implications: This study has two implications: First, when IFRS implementation shows an important role in improving the quality of earnings, the policymakers should encourage companies to fully adopt the IFRS. Second, taking into account that CSR is an important factor in increasing earnings quality, policy makers need to increase the role of disclosure of CSR information from voluntary to mandatory. Novelty/Originality: As far as the knowledge of the authors, research that has been conducted specifically on plantations that have certain characteristics in the application of IAS 41 and CSR problems in two countries are quite complicated and have not been done by many researchers.